Hypoxia Medical Academy
"Hypoxia Medical Academy" it is a Russian company founded in 1989. The main activity of "Hypoxia Medical Academy" is developing and introducing a new trend in medicine - the method of Interval Hypoxytherapy / Hypoxytraining (IHT).